Macrophages in Bone Homeostasis - Kong, Lingbo; Wang, Youhan; Smith, Wanli; Hao, Dingjun (Current Stem Cell Research & Therapy, 2019)
Aberrant or prolonged immune responses has been proved to be involved in bone homeostasis. As a component of the innate immune system, macrophages play a critical role in bone homeostasis. Conventionally, according to response to the various panel of stimuli, macrophages can be plastically classified into two major phenotypes: M1 and M2. M1 macrophages are generally proinflammatory, whereas M2 are anti-inflammatory. Although studies demonstrated that both M1 and M2 phenotypes have been implicated in various inflammatory bone diseases, their direct role in bone homeostasis remains unclear. Thus, in this review, we briefly discuss the term “osteoimmunology”, which deals with the crosstalk and shared mechanisms of the bone and immune systems. In addition, we overview M1 and M2 macrophages for their role in osteoclastogenesis and osteogenesis as well as relevant signaling cascades involved.
Keywords: Bone homeostasis